Gender, poverty and disability in the National Action Plan for Food and Nutrition 2017-2019 of Indonesia and ways forward - Ramani, Gayathri V.; Go, Ara; Olney, Deanna K. (International Food Policy Research Institute, 2020)
Social inclusion is defined by the World Bank Group as the process of improving the terms of individuals and groups to take part in society, and the process of improving the ability, opportunity, and dignity of those disadvantaged based on their identity to take part in society. Groups can be excluded based on several characteristics or life circumstances. These include poverty, gender, age, religion, ethnicity and disability, among others. Within a country context, social exclusion implies that excluded groups are not able to fully participate in their country’s political, economic, and social life and often are unable to fully benefit from programs and policies intended to benefit the population at large. As Indonesia’s economy continues to grow, it is essential that issues of social inclusion be considered in nutrition-related policies and programs. This is especially important as often socially excluded groups are those most at risk of health and nutrition problems.